Pengaruh Motivasi Belajar terhadap Hasil Belajar Siswa Pendidikan Agama Islam Setingkat Madrasah Tsanawiyah: Pendahuluan,Metode Penelitian,Hasil Pembahasan - Didit Darmawan; Muhammad Izzul Haq (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study is grounded in the empirical phenomenon of declining learning motivation among Madrasah Tsanawiyah (MTs) students, which has implications for suboptimal learning outcomes, particularly in the subject of Islamic Religious Education. Learning motivation is understood as an educational psychology construct that plays a crucial role in guiding students’ learning engagement across the cognitive, affective, and psychomotor domains. This study aims to systematically examine the relationship between learning motivation and the learning outcomes of MTs students based on a synthesis of empirical findings from previous research. The method used is a qualitative approach with a systematic literature review design. Data were sourced from accredited national scientific journal articles as well as academic theses (undergraduate and master’s theses) spanning from 2020 to the present, collected via Google Scholar and university repositories. Analysis techniques included data reduction, thematic categorization, and interpretive synthesis to produce a systemic understanding. The results of the study indicate that learning motivation has a significant and determinative influence on variations in the learning outcomes of MTs students. Intrinsic motivation tends to be more consistent in supporting sustained academic achievement compared to extrinsic motivation, while also reinforcing the internalization of Islamic values. The study’s findings confirm that learning motivation is a central variable in optimizing learning outcomes, making its enhancement an essential prerequisite for pedagogical design at the MTs level.